Magnetotelluric investigations over geothermal provinces of India: an overview - Prabhala, Bhakhara Venkata Subba Rao; Pachigolla, Venkata Vijaya Kumar; Dornadula, Chandrasekharam; Deshmukh, Vasu; Singh, Ajay Kishore (My University, 2023)
Magnetotelluric (MT) and audio-magnetotelluric (AMT) studies are sensitive to the geothermal fluids filling the faults and/ or fracture zones of the geothermal system. In India, MT/AMT studies have been carried out in NW Himalayas, central, eastern, and western India. In other areas, detailed MT/AMT studies need to be expedited. This review paper presents the art of geothermal exploration in India by using MT/AMT techniques and identifies potential zones that can be exploited for power generation and direct application. Reservoir characteristics, carbon emissions reduction methods, and levelised cost factor are also discussed.
Keywords: Geothermal zones; Magnetotellurics; Conductivity anomaly